New chemotherapy regimens and biomarkers for Chagas disease: the rationale and design of the TESEO study, an open-label, randomised, prospective, phase-2 clinical trial in the Plurinational State of Bolivia. Issue 12 (31st December 2021) - Alonso-Vega, Cristina; Urbina, Julio A; Sanz, Sergi; Pinazo, María-Jesús; Pinto, Jimy José; Gonzalez, Virginia R; Rojas, Gimena; Ortiz, Lourdes; Garcia, Wilson; Lozano, Daniel; Soy, Dolors; Maldonado, Rosa A; et al.
Abstract : Introduction: Chagas disease (CD) affects 7 million people worldwide. Benznidazole (BZN) and nifurtimox (NFX) are the only approved drugs for CD chemotherapy. Although both drugs are highly effective in acute and paediatric infections, their efficacy in adults with chronic CD (CCD) is lower and variable. Moreover, the high incidence of adverse events (AEs) with both drugs has hampered their widespread use. Trials in CCD adults showed that quantitative PCR (qPCR) assays remain negative for 12 months after standard-of-care (SoC) BZN treatment in 80% patients. BZN pharmacokinetic data and the nonsynchronous nature of the proliferative mammal-dwelling parasite stage suggested that a lower BZN/NFX dosing frequency, combined with standard or extended treatment duration, might have the same or better efficacy than either drug SoC, with fewer AEs. Methods and analysis: New ThErapies and Biomarkers for ChagaS infEctiOn (TESEO) is an open-label, randomised, prospective, phase-2 clinical trial, with six treatment arms (75 patients/arm, 450 patients). Primary objectives are to compare the safety and efficacy of two new proposed chemotherapy regimens of BZN and NFX in adults with CCD with the current SoC for BZN and NFX, evaluated by qPCR and biomarkers for 36 months posttreatment and correlated with CD conventional serology. Recruitment of patients was initiated on 18 December 2019 and on 20 May 2021, 450 patients (study goal) were randomised among the six treatment arms. The treatment phase was finalised on 18 August 2021. Secondary objectives include evaluation of population pharmacokinetics of both drugs in all treatment arms, the incidence of AEs, and parasite genotyping. Ethics and dissemination: The TESEO study was approved by the National Institutes of Health (NIH), U.S. Food and Drug Administration (FDA), federal regulatory agency of the Plurinational State of Bolivia and the Ethics Committees of the participating institutions. The results will be disseminated via publications in peer-reviewed journals, conferences and reports to the NIH, FDA and participating institutions. Trial registration number: NCT03981523 .